Inhibition of Gluconeogenesis by Boldine in the Perfused Liver: Therapeutical Implication for Glycemic Control - Laís Cristina Lima Silva; Gustavo Henrique de Souza; Vanesa de Oliveira Pateis; Ana Paula Ames-Sibin; Beatriz Paes Silva; Lívia Bracht; Jurandir Fernando Comar; Rosane Marina Peralta; Adelar Bracht; Anacharis Babeto Sá-Nakanishi (International Journal of Hepatology)
The alkaloid boldine occurs in the Chilean boldo tree (Peumus boldus). It acts as a free radical scavenger and controls glycemia in diabetic rats. Various mechanisms have been proposed for this effect, including inhibited glucose absorption, stimulated insulin secretion, and increased expression of genes involved in glycemic control. Direct effects on glucose synthesis and degradation were not yet measured. To fill this gap, the present study is aimed at ensuring several metabolic pathways linked to glucose metabolism (e.g., gluconeogenesis) in the isolated perfused rat liver. In order to address mechanistic issues, energy transduction in isolated mitochondria and activities of gluconeogenic key enzymes in tissue preparations were also measured. Boldine diminished mitochondrial ROS generation, with no effect on energy transduction in isolated mitochondria. It inhibited, however, at least three enzymes of the gluconeogenic pathway, namely, phosphoenolpyruvate carboxykinase, fructose-bisphosphatase-1, and glucose 6-phosphatase, starting at concentrations below 50 μM. Consistently, in the perfused liver, boldine decreased lactate-, alanine-, and fructose-driven gluconeogenesis with IC50 values of 71.9, 85.2, and 83.6 μM, respectively. Conversely, the compound also increased glycolysis from glycogen-derived glucosyl units. The hepatic ATP content was not affected by boldine. It is proposed that the direct inhibition of hepatic gluconeogenesis by boldine, combined with the increase of glycolysis, could be an important event behind the diminished hyperglycemia observed in boldine-treated diabetic rats.